The political context of national digital health policy formulation: Insights from Ghana - Acquah, Akwesi; Nel-Sanders, Danielle (Asian Development Policy Review, 2025)
Globally, governments are formulating national digital health policies to guide the implementation and regulation of digital technology in their health sectors. Although sufficient evidence focusing on the technical context of formulating national digital health policies exists, research focusing on the political context of national digital health policies and the role of political actors during the development of national digital health policies is limited. This study sought to bridge this gap by investigating the political context of Ghana’s formulation of national digital health policy and the role of key political actors in the policy decision-making process. The study adopted a qualitative research approach involving data triangulation of semi-structured interviews with political elites involved in the national digital health formulation process and a document analysis of Ghana’s digital health policy. The study used thematic and content analyses as well as systems theory constructions to show that Ghana's digital health policy development is influenced by structured policy inputs, consistent procedures, measurable results, and strong feedback systems. The study recommends a paradigm shift from the vertical approach of national digital health policymaking to a lateral approach, which brings key stakeholders on board from the onset of the process for developing digital health policy.